P‐Doped MoO2/Porous Ni Self‐Supported Catalyst for Electrocatalytic Hydrogen Evolution in Alkaline Solution. Issue 11 (21st September 2022) - Xu, Ziyi; Teng, Xianggui; Dou, Xiaoyi; Wu, Yong; Wei, Jinchao; Chen, Qizhi; Zhang, Jian; Zeng, Julan; Yu, Linping
Abstract : Constructing integrated electrocatalysts free from binder is recognized as a promising approach to promote the long‐term efficiency of hydrogen evolution through water electrolysis. Herein, the in situ growth of MoO2 on a porous Ni substrate followed by phosphorus doping is reported to generate self‐supported P‐doped MoO2 /porous Ni electrocatalyst for hydrogen evolution reaction. The porous Ni substrate provides a large specific surface area and highly accessible channels for accommodating the active nanoparticles, which achieves an ultralow overpotential of 81 mV at 10 mA cm −2, a small Tafel slope of 99 mV decade −1, and exceptionally high durability for 24 h. The excellent performance of P‐doped MoO2 /porous Ni is mainly attributable to the efficient electrolyte diffusion, fast emission of gas bubbles, and enhanced electrical conductivity brought by porous Ni substrate and the highly active sites. This self‐supported catalyst is distinct and superior to the conventional powdery catalysts in developing new energy conversion technologies. Abstract : Self‐supporting hierarchically porous P‐doped MoO2 /porous (Prs) Ni is developed as a cost‐effective and robust electrocatalyst for hydrogen evolution reaction with reduced overpotentials in alkaline solution.